'Sport as a Resource Caravan': Understanding How Adults Utilize Sport as a Developmental Tool. Issue 4 (2nd December 2022) - Walsh, David W.; Green, B. Christine; Harrison, Tracie; Bowers, Matthew T.
Abstract: Sport-for-development research consistently focuses on studies of macro level policy, meso level community development, and micro level individual development. However, individual development has largely focused on positive youth development through sport. Further, development outcomes have been studied with reference to a single program. This study examines the aggregate value of sport in development across the lifespan. Specifically, it examines the role of sport to facilitate or hinder adaptation to life transitions. A life-history, thematic analysis with data from semi-structured interviews and life maps with 15 participants aged 50 and older was conducted. Results revealed sport's role as an effective resource provider via social exchanges when participants faced a disruption caused by a life event transition. This is significant as sport may help provide access to scarce resources theorized to alter the fundamental developmental process of an individual's life-course (i.e. transitions). With this research, innovative sport designs and intentional sport management strategies that influence developmental trajectories in adults could emerge. Practical suggestions for program design and marketing are recommended.